Psychological Fluency and Its Relationship with Creative Teaching Practices among Physical Education Instructors in Light of Gender and Educational Environment Variables - Suhair Rahman Salman (Jurnal Ilmiah STOK Bina Guna Medan, 2026)
The problem addressed in this study stems from the researcher’s observations as a teacher and through visits to various schools in both rural and urban areas, for boys and girls, where a noticeable discrepancy was found in the level of creative teaching practices among physical education teachers. This variation may be attributed to individual differences in psychological fluency, demographic characteristics, or environmental factors such as gender and the nature of the educational environment. The objectives of the study were to identify the levels of psychological fluency and creative teaching practices among physical education teachers in light of gender and educational environment variables, and to examine the relationship between these two constructs. The study adopted a descriptive design with survey and correlational approaches. The population consisted of 759 physical education teachers in Dhi Qar Governorate, comprising 376 males and 383 females, with 310 teachers working in rural schools and 449 in central schools. The total sample included 540 teachers divided into exploratory, construction, and application samples. The results revealed a strong positive correlation between psychological fluency and creative teaching practices, indicating that teachers with higher levels of psychological fluency tend to exhibit more creative teaching performance. It can be concluded that psychological fluency serves as a significant predictor of creative teaching practices, suggesting that enhancing psychological fluency may improve teachers’ creative teaching performance.